Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Kejuruan TJKT Kelas X TJKT 2 SMK Negeri 3 Padang - Salwa Rahmadhini (SAFE-Network, 2026)
This study aims to improve student learning outcomes using the Project Based Learning model for Vocational Basics of TJKT Class X TJKT 2 SMK Negeri 3 Padang in the 2023/2024 academic year. The method used in this study is the classroom action research method. The selection of the classroom action research method is based on the basis of the problem and research objectives that require improvements/increases (follow-up) in the classroom with action research procedures using a cycle model consisting of four parts, namely planning, implementation, observation, and reflection. The research subjects were 36 students of class X TJKT 2 SMK Negeri 3 Padang. The results of the study showed that the percentage of completeness of learning outcomes of class X TJKT 2 students in Cycle I was 78% and in Cycle II was 94%. The conclusion of this study is that the Basic Vocational Learning of TJKT which is carried out using the Project Based Learning learning model makes students more active and creative in learning and the values ​​obtained by students in the Basic Vocational Learning of TJKT through the use of the Project Based Learning learning model have increased from cycle I to cycle II by 16%.